Evaluation of late cardiac effects after multisystem inflammatory syndrome in children - Rik De Wolf; Mahmoud Zaqout; Mahmoud Zaqout; Kaoru Tanaka; Laura Muiño-Mosquera; Gerlant van Berlaer; Kristof Vandekerckhove; Wendy Dewals; Daniël De Wolf; Daniël De Wolf (Frontiers Media S.A., 2023)
IntroductionMultisystem inflammatory syndrome in children (MIS-C) is associated with important cardiovascular morbidity during the acute phase. Follow-up shows a swift recovery of cardiac abnormalities in most patients. However, a small portion of patients has persistent cardiac sequelae at mid-term. The goal of our study was to assess late cardiac outcomes of MIS-C.MethodsA prospective observational multicenter study was performed in children admitted with MIS-C and cardiac involvement between April 2020 and March 2022. A follow-up by NT-proBNP measurement, echocardiography, 24-h Holter monitoring, and cardiac MRI (CMR) was performed at least 6 months after MIS-C diagnosis.ResultsWe included 36 children with a median age of 10 (8.0-11.0) years, and among them, 21 (58%) were girls. At diagnosis, all patients had an elevated NT-proBNP, and 39% had a decreased left ventricular ejection fraction (LVEF) (<55%). ECG abnormalities were present in 13 (36%) patients, but none presented with arrhythmia. Almost two-thirds of patients (58%) had echocardiographic abnormalities such as coronary artery dilation (20%), pericardial effusion (17%), and mitral valve insufficiency (14%). A decreased echocardiographic systolic left ventricular (LV) function was detected in 14 (39%) patients. A follow-up visit was done at a mean time of 12.1 (±5.8) months (range 6-28 months). The ECG normalized in all except one, and no arrhythmias were detected on 24-h Holter monitoring. None had persistent coronary artery dilation or pericardial effusion. The NT-proBNP level and echocardiographic systolic LV function normalized in all patients, except for one, who had a severely reduced EF. The LV global longitudinal strain (GLS), as a marker of subclinical myocardial dysfunction, decreased (z < −2) in 35%. CMR identified one patient with severely reduced EF and extensive myocardial fibrosis requiring heart transplantation. None of the other patients had signs of myocardial scarring on CMR.ConclusionLate cardiac outcomes after MIS-C, if treated according to the current guidelines, are excellent. CMR does not show any myocardial scarring in children with normal systolic LV function. However, a subgroup had a decreased GLS at follow-up, possibly as a reflection of persistent subclinical myocardial dysfunction.